The role of pH in symptomatic relief and effective treatment of gastroesophageal reflux disease - Anita Gąsiorowska (Gastroenterology Review)
Gastroesophageal reflux disease (GERD) is a condition in which gastroduodenal contents pass into the oesophagus and cause troublesome symptoms and complications. The aetiopathogenesis of gastroesophageal reflux disease is complex and multifactorial. Acid reflux plays an important role in the GERD pathogenesis, both in erosive and non-erosive reflux disease. Reduction of GERD symptoms and mucosal healing correlates with the number of hours that intragastric acid is suppressed to a pH > 4.0. Mucosal healing was achieved in most of patients who received different types of proton pump inhibitors, but only in 50% of those who received H2 blockers. These findings seem to be best accounted for by differences in the duration and degree of acid suppression achieved by different classes of drugs and perhaps between agents within those classes.